LEADER IDEOLOGY IN POST-SOVIET TAJIKISTAN - HORÁK, Slavomir (CENTRAL ASIA AND THE CAUCASUS, 2009)
Ideology is one of the foundations of authoritative regimes and forms the image of their leaders. Using Uzbekistan as an example, A.arch comes to the conclusion that the ideological system imposed by the state has a tangible impact on society, even one that has already lived at one time under the communist ideology.1 Based on an analysis of several special features of the development of the post-Communist countries (and several others), the conclusion is drawn that during a political regime change, the population can be ideologically “reset.” After a new ideology has been repeatedly fed to the people over the span of several years, it becomes a conscious or subconscious element of society’s mindset.2 Thus ideology plays a significant role in state- and nation-building, particular after the formation of new states or territorial units. The new system forms in several interdependent dimensions. The first, chronologically, is historical ideology. The existence of a historical past that goes back into antiquity sets a nation or nationality above others (usually its neighbors).research studies in this area are leading to the rapid development of archeology and myth creation about antiquity. Another goal of historical ideology is searching for the most significant periods in history of a certain territory (or nation) which are frequently associated with certain out-standing personalities: “great” nations are regard-ed as the predecessors of present-day territorial units, and heroes are associated with the leaders of the most recent times (presidents or monarchs),